2013
DOI: 10.1186/2193-1801-2-300
|View full text |Cite
|
Sign up to set email alerts
|

Cohort profile: mental health following extreme trauma in a northern Ugandan cohort of W ar-A ffected Y outh S tudy (The WAYS Study)

Abstract: War experiences are associated with the risk of long-term mental health problems. The War-affected Youths (WAYS) Study comprises a cohort of 539 youths (61% female) aged between 18 to 25 (at baseline) randomly sampled from the population of war-affected youths in northern Uganda. The study aims to chart the trajectory of long-term mental health consequences of war and the roles of individual, family, and community contextual risk and protective factors in influencing the course of mental health using Social Ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 29 publications
1
53
0
Order By: Relevance
“…Trauma exposure was measured using the United Nations Children’s Fund (UNICEF) War Trauma Screening Scale, which was originally developed for Bosnia and Herzegovina but has been adapted for use in African war-affected youth (Amone-P’Olak et al, 2013). The instrument consists of items relating to personal injury (six items), witnessing violence (11 items), injuries and threats to self (five items), deaths (seven items), physical threats to loved ones (four items), material losses (four items), harm to loved ones (four items), separation (two items), displacement (five items), participating in armed groups (four items) and sexual abuse (three items).…”
Section: Methodsmentioning
confidence: 99%
“…Trauma exposure was measured using the United Nations Children’s Fund (UNICEF) War Trauma Screening Scale, which was originally developed for Bosnia and Herzegovina but has been adapted for use in African war-affected youth (Amone-P’Olak et al, 2013). The instrument consists of items relating to personal injury (six items), witnessing violence (11 items), injuries and threats to self (five items), deaths (seven items), physical threats to loved ones (four items), material losses (four items), harm to loved ones (four items), separation (two items), displacement (five items), participating in armed groups (four items) and sexual abuse (three items).…”
Section: Methodsmentioning
confidence: 99%
“…Thirty-six percent were found to fulfill the criteria for PTSD, depression, and anxiety simultaneously [13]. A longitudinal study, the War-Affected Youth Study (WAYS), by Amone-P'Olak et al [14], found that war experiences were significantly associated with difficulties performing daily activities and tasks (t=-2.62, p<.001), especially for females compared to male participants (t=-2.62, p<.05). Overall, women were more at risk of long-term mental health outcomes compared to men [14].…”
Section: Ugandamentioning
confidence: 99%
“…A longitudinal study, the War-Affected Youth Study (WAYS), by Amone-P'Olak et al [14], found that war experiences were significantly associated with difficulties performing daily activities and tasks (t=-2.62, p<.001), especially for females compared to male participants (t=-2.62, p<.05). Overall, women were more at risk of long-term mental health outcomes compared to men [14]. Due to the extent of trauma found in previous studies and the prolonged period of the war, we presuppose that northern Uganda has a relevant population for the study of C-PTSD.…”
Section: Ugandamentioning
confidence: 99%
See 2 more Smart Citations